UTILIZATION OF MULTIMODAL TEXTS OF STORYBOOKS BASED ON HEYZINE FLIPBOOK IN READING LITERACY - Nurlaeli, Nisa; Arfiyanti, Riskha; Nuryanti, Mira (Universitas Negeri Makassar, 2025)
This study evaluates the potential of multimodal digital children's stories based on the Heyzine flipbook to enhance reading literacy among elementary school students. Using a descriptive qualitative approach through an integrative literature review, the study analyzes various sources related to children's story texts, digital media, heyzine flipbook, and multimodal literacy. The data collection techniques in this study were conducted through a literature study and direct exploration of the features of the Heyzine flipbook. The data were analyzed using content analysis techniques through the identification of explicit and implicit information, selection of relevant sources, and synthesis of findings to produce conclusions. The findings indicate that the interactive features of the heyzine flipbook can effectively increase students' reading interest, engagement, and comprehension. The integration of multiple modes within a single digital platform supports 21st-century literacy learning in a more engaging and meaningful way, aligned with the literacy reinforcement goals of the Merdeka Curriculum.